Pengaruh Pemasaran Digital dan Harga terhadap Keputusan Pembelian Warung Makan Bebek Gledek di Jakarta Timur - Abdurrohim, Abdurrohim; Sukirno, Sukirno (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
At a spreading time of the Covid-19 virus around the world, the companies across Indonesia were affected because of the Covid-19 such as hard to adapt and many are struggling to protect their employees from losing their jobs. The Micro, Small, and Medium Enterprises or UMKM in Indonesia is one of the most affected by the Covid-19 pandemic. With many shopping centers, food stalls and other industries that must close due to Large-Scale Social Restrictions (PSBB) to break the chain of the spreading of the COVID-19 virus, causing many UMKM industry players switch to do selling through digital marketing. This study aimed to (a) determine the effect of digital marketing on the purchase decision for Warung Makan Bebek Gledek during the Covid-19 pandemic in East Jakarta. (b) determine the effect of price on the purchase decision for Warung Makan Bebek Gledek during the Covid-19 pandemic in East Jakarta. (c) determine the effect of digital marketing and price on the purchase decision for Warung Makan Bebek Gledek in East Jakarta. The method used was quantitative research, which involves 60 respondents as a sample using a questionnaire. Thecollected data were scored and then analyzed using the SPSS (Statical Program For Social Science) 26.0 for Windows program. The results showed that the effect of digital marketing and price on the purchase decision of Warung Makan Bebek Gledek during theCovid-19 pandemic in East Jakarta based on the coefficient of determination test showed the amount of 51,3%. The rest was affected by other factors.